Costos de producción por procesos y su incidencia en la rentabilidad de la empresa tabacalera san mateo, año 2019. - Valenzuela Luna, Javier Armando (2020)
Profitability continues to be the most important motivation for those who invest capital in a company. Knowing the factors on which profitability depends, constitutes an irreplaceable instrument to control it. On the other hand, the reduction of costs obeys both internal causes (profit maximization), and external competitiveness. Management accounting offers techniques for cost reduction and value creation, which contribute to raising the financial profitability of the company by improving the profit margin and market share. The Tabacalera San Mateo c. Ltda. Tabacama, was incorporated and exists under the Ecuadorian laws since its inscription in the Mercantile Registry on August 1, 2012 with a duration of fifty years; its main domicile is in the canton Quevedo, Province of Los Ríos. The Company's corporate purpose is to carry out prospecting, research and soil analysis studies for planting; exploration, exploitation, production, export, import, and commercialization of agricultural, mining, timber, industrial, cattle, swine, poultry and aquaculture products; provide consulting services in the fields of tobacco, banana, oil palm, floricultural agricultural administration to all kinds of companies. Its main source of income is the production of tobacco leaf. It should be noted that the total production obtained is sold to the company from abroad Grand Island Group, S, R, L, (domiciled in the Dominican Republic); therefore, the financial and business position underway depends fundamentally on the links and agreements established with this entity.